2020
DOI: 10.1080/09581596.2020.1725443
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive health care for LGBTQ+ youth: support, belonging, and inclusivity labour

Abstract: Drawing on findings from a study of two social generations of gender and sexuality diverse Australians, this paper offers a critical analysis of expectations and experiences of inclusive health care for LGBTQ+ youth. Data were collected by means of individual and focus group interviews with people from two different social generations who grew up in regional or urban Australia: those born in the 1970s (n=50) and those born in the 1990s (n=71). Data were analysed inductively to develop insights into what inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Just some of these changes include: the achievement of marriage equality in many settings (Pew Research Centre, 2019), the increasing visibility of health advocacy by and for trans and gender diverse people (Callander et al, 2020), the availability of pre-exposure prophylaxis (PrEP) and other biomedical interventions to prevent HIV transmission (Newman et al, 2019), and a move away from community socialising at commercial leisure venues (bars, clubs, sex-on-premises venues and so on) (Drysdale, 2019). These, (Newman et al, 2020). As such, closer connections between community-based research on LGBTQ needs, and the interventions developed to respond to those needs, coupled with changes in healthcare provider attitudes towards LGBTQ people and understandings of their health risks and intervention needs, are essential if the targeting of cancer prevention and screening interventions is to be truly effective.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
See 2 more Smart Citations
“…Just some of these changes include: the achievement of marriage equality in many settings (Pew Research Centre, 2019), the increasing visibility of health advocacy by and for trans and gender diverse people (Callander et al, 2020), the availability of pre-exposure prophylaxis (PrEP) and other biomedical interventions to prevent HIV transmission (Newman et al, 2019), and a move away from community socialising at commercial leisure venues (bars, clubs, sex-on-premises venues and so on) (Drysdale, 2019). These, (Newman et al, 2020). As such, closer connections between community-based research on LGBTQ needs, and the interventions developed to respond to those needs, coupled with changes in healthcare provider attitudes towards LGBTQ people and understandings of their health risks and intervention needs, are essential if the targeting of cancer prevention and screening interventions is to be truly effective.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…This review examined peer-reviewed academic literature published from 1 January 2014 to 30 January 2020 to determine evidence of acceptability, feasibility and efficacy of cancer prevention and screening interventions for LGBTQ communities. This date range was selected to ensure that only the most recent and relevant research was included, given there has been considerable social and political change in the last few decades which affects the ways in which LGBTQ communities engage with health promotion and cancer screening and prevention (Newman et al, 2020). Relevant literature was identified by searching key databases with consistent search parameters and using EndNote as a data management tool (see Table 1 for a list of databases and search parameters, and Figure 1 for a chart of the selection process).…”
Section: Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review found that research was more likely to identify barriers to accessing mental health support rather than facilitators to encourage engagement ( Wilson & Cariola, 2019 ). In addition, there is an absence of focus on intersectional factors such as ethnicity, socioeconomic status and disability in LGBTQ+ ​youth mental health care ( Craig, McInroy, Austin, Smith, & Engle, 2012 ; Newman et al., 2020 ; Riggs & Treharne, 2017 ). Newman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving health equity for trans people will require an ambitious combination of political will, community support and robust health systems. Even in Australia, where there is arguably a well-developed approach to providing gender affirming forms of health care, access depends on age, location, citizenship status, and financial capacity (particularly to gender affirming surgery which is not subsidised by the publicly funded health system), as well as the intensive labour of health care consumers in identifying and securing access to appropriate care providers (Davies, 2019;Newman, Prankumar et al, 2020). Too often, trans people report encounters with clinicians and allied health professionals who are unprepared for providing the care that is needed.…”
Section: Editorial Introductionmentioning
confidence: 99%